People from the Stars - John Joseph Mathews (Symphony in the Flint Hills, 2019)
Introduction: Wahzhazhe come from the stars By their choice, not by falling Or being thrown out Of the heavenly bars like Satan Into Europe, And we are invited back whenever we may choose to go... (Excerpted from: The Osages, John Joseph Mathews, published by University of Oklahoma Press, 1981.)